The good infinite in early German romanticism - Burda, J (2017)
In this dissertation I challenge the 'standard' reading of early German romanticism, according to which the movement is most fundamentally characterized by unfulfilled longing, infinite approximation and nostalgic despair. Against this 'defeatist reading' I put forward a ‘conciliatory reading’ according to which the romantics advocate a harmonious relationship between ourselves and the world. The reading I offer is centred on the idea of 'good infinity', an idea long associated with Hegel but one which I argue the romantics (especially Schlegel) anticipated. A good infinity is united with, rather than opposed to, finitude. This dissertation sets out to show how this romantic conception of infinity underlies major aspects of romanticism such as 'incomprehensibility', 'irony', and the method of 'Wechselerweis'. In chapter 1, I argue that the romantics are neither pre-critical idealists continuing the Spinozistic heritage (the view of Frederick Beiser), nor Kantian skeptics replacing the 'thing-in-itself' with the Absolute (the view of Manfred Frank). On the reading I advance, the romantics are forbears to the phenomenological tradition. In chapter 2, I argue that Schlegel's recurring references to 'incomprehensibility', or Novalis' appraisal of 'the night' in his Hymns, are intended as 'positive' contributions in that they ask us to acknowledge and accept, rather than commiserate and reject, an incomprehensible dimension to the world. In chapter 3, I argue that ‘good infinity’ is implied in the method of ‘Wechselerweis' because of its emphasis on a reciprocal relationship. I survey various philosophical attempts to classify romanticism and show how I take my reading to preserve the various truths contained in each. In chapter 4, I distinguish the romantics' version of 'good infinity' from that of Hegel. I use various examples to motivate and describe a first personal sense of commitment that romantic irony, understood as feeling at the same time 'finite and infinite', makes available. Together these chapters support my claim that interpreting infinity to entail unreachability amounts to a limited and ultimately unfaithful reading of the early German romanticist project. With 'good infinity' I offer a way out of those limitations.